1970
DOI: 10.3329/bjmm.v4i1.8470
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax: An Emerging Zoonotic Disease in Bangladesh

Abstract: DOI: http://dx.doi.org/10.3329/bjmm.v4i1.8470BJMM 2011; 4(1): 46-50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 19 publications
2
43
0
Order By: Relevance
“…Anthrax is now an emerged zoonotic disease of Bangladesh and it is enzootic also for long time (Ahmed et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Anthrax is now an emerged zoonotic disease of Bangladesh and it is enzootic also for long time (Ahmed et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It emerged as a zoonotic disease in this country during 2009(Ahmed et al, 2010. The disease caused by the bacterium Bacillus anthracisis primarily a disease of ruminants and was one of the main causes of uncontrolled mortality in cattle, sheep, goats, horses and pigs worldwide until the development of an effective vaccine and introduction of antibiotics (Ahmed et al, 2010). Anthrax was periodically reported both in animals and humans in between 1949 and 1986.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh, the disease was sporadically reported in animals and human until 2009 (Ahmed et al, 2010). In recent years, the disease occurred repeatedly; the outbreaks indicated that the disease is no longer sporadic, rather enzootic in Bangladesh (Ahmed et al, 2010;Fasanella et al, 2013;Ahsan et al, 2013).In different areas of Bangladesh, 14 outbreaks occurred during the period of August 2009 to October 2010, affecting 140 animals and subsequently to 273 humans. This created a panic to the people.…”
Section: Introductionmentioning
confidence: 99%